Sirtuins as regulators of apoptosis induced proliferation in the eye of Drosphila melanogaster - Hebesberger, Philipp (Jihočeská univerzita, 2023)
The effect of Sirtuins on the activity of mTOR, a regulator of apoptosis induced proliferation, was studied in the eye of Drosophila melanogaster. The eye sizes of wildtype flies and mutants with knockdown of a Sirtuin, respiratory Complex I or both were compared by quantifying the amount of red eye pigment with colorimetry.
Sirtuins as regulators of apoptosis induced proliferation in the eye of Drosphila melanogaster